1990
DOI: 10.1246/bcsj.63.1287
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of High Transition Temperature Superconducting Oxides

Abstract: Typical high transition temperature (high-Tc) superconducting oxides were used as electrodes in order to investigate their electrochemical behavior at room temperature. Chemical stability of these materials in various solutions was also tested. These superconducting oxides were stable in nonaqueous solutions, but is was very difficult to protect electrical contacts from the solvents because of porous structures of these oxides. These materials were rather stable in highly concentrated alkaline solutions while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11] In addition, some authors have found some of these methods to be suitable for determining the Cu(III)/ Cu(II) ratio. By using a rotating ring-disk electrode, Rosamilia et al investigated a YBaCuO superconductor that was placed on a disk in various acidic solutions.12 Other authors have used cyclic voltammetry to measure the Cu(III) content in highly alkaline aqueous solutions' 3,14 and non-aqueous media.15,16 Other electroanalytical methods used for this purpose include chronopotentiometry" and coulometric titratlons.l8, 19 The carbon-paste electrode is another useful approach to the problem.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] In addition, some authors have found some of these methods to be suitable for determining the Cu(III)/ Cu(II) ratio. By using a rotating ring-disk electrode, Rosamilia et al investigated a YBaCuO superconductor that was placed on a disk in various acidic solutions.12 Other authors have used cyclic voltammetry to measure the Cu(III) content in highly alkaline aqueous solutions' 3,14 and non-aqueous media.15,16 Other electroanalytical methods used for this purpose include chronopotentiometry" and coulometric titratlons.l8, 19 The carbon-paste electrode is another useful approach to the problem.…”
mentioning
confidence: 99%